Impaired memory consolidation during sleep in patients with functional memory disorder - Puetz, Julia; Grohmann, Svenja; Metternich, Birgitta; Kloepfer, Corinna; Feige, Bernd; Nissen, Christoph; Riemann, Dieter; Hüll, Michael; Hornyak, Magdolna (Biological psychology, 2011)
▶ Patients with FMD show an impairment of declarative memory consolidation during sleep. ▶ Spectral analysis of sleep-EEG indicates an increased cortical excitation in FMD. ▶ A hyperarousal state in FMD might contribute to impaired memory consolidation. Functional memory disorder (FMD) is characterized by mnestic and attentional deficits without symptoms of mild cognitive impairment or dementia. FMD usually develops in subjects with high psychosocial stress level and is classified to the somatoform disorders. We assessed memory performance (procedural mirror tracing task, declarative visual and verbal memory task) and other cognitive functions before and after one night of sleep in 12 FMD patients (mean age: 51.7 yrs, 7 females) and 12 healthy subjects matched for age, gender and IQ. Memory performance and other neurocognitive tasks did not differ between the groups at baseline. After one night of sleep, FMD patients showed an impairment of declarative memory consolidation compared to healthy subjects (visual task: p = 0.004; verbal task: p = 0.039). Spectral analysis of sleep-EEG indicated an increased cortical excitation in FMD. We hypothesize that a hyperarousal state in FMD might contribute to sleep disturbance implicating negative effects on declarative memory consolidation.